IMPLEMENTATION OF ACUPRESSURE IN REDUCING LABOR PAIN - Atriani, Delvy; Septadina, Indri Seta (International Islamic Medicine Forum, 2025)
Labor pain is a multifaceted physiological phenomenon and is frequently one of the most arduous elements of the birthing process. If labor pain is unmanaged, it may result in complications that are not only distressing for the mother but also potentially hazardous for the fetus. Acupressure is a technique that can be used to reduce the intensity of labor pain. Acupressure is a traditional Chinese medicine practice that involves applying pressure to specific points on the body. This article will explore the implementation of acupressure in alleviating labor pain from various credible scientific sources. Research has shown that applying pressure to points such as LI4, SP6, GB21, and BL32 reduces pain intensity during labor, making acupressure a non-pharmacological management option during childbirth. ABSTRAK Nyeri persalinan merupakan pengalaman fisiologis yang kompleks dan seringkali menjadi salah satu aspek paling menantang dalam proses kelahiran. Apabila nyeri dalam persalinan tidak diatasi, maka akan menimbulkan masalah yang tidak hanya menyakitkan pada Ibu bersalin, akan tetapi juga berpotensi mengancam jiwa janinnya. Salah satu teknik yang dapat dilakukan untuk mengurangi intensitas nyeri persalinan adalah dengan memberikan akupresur. Akupresur merupakan pengobatan tradisional Tiongkok, yang melibatkan penekanan pada titik-titik tertentu di tubuh. Artikel ini akan membahas lebih mendalam mengenai implementasi akupresur dalam mengurangi nyeri persalinan dari berbagai sumber ilmiah yang terpercaya. Penekanan pada titik LI4, SP6, GB21 dan BL32 telah terbukti mengurangi intensitas nyeri pada persalinan, sehingga implementasi akupresur untuk mengurangi nyeri persalinan merupakan salah satu tatalaksana non farmakologis yang dapat diberikan pada proses persalinan.